The Effect of Compensation and Job Satisfaction on Employee Productivity - Sitorus, Santa Lusianna; Hidayat, Aviv (Journal of International Conference Proceedings, 2023)
Employee productivity is very important for companies to win the competition in the industry. Compensation and job satisfaction are supporting factors for employee productivity to produce maximum and quality production.  This study intends to decide the impact of compensation and job satisfaction on employee productivity at PT. SEIV Indonesia. In this study, secondary data was used and tests were carried out using the SPSS program to determine the most influential variables.  The results of this study demonstrate that: compensation have a positive and critical impact on productivity of employee and jobs satisfaction have a positive and critical impact on productivity of employee.  The advice that can be given is that companies need to maintain compensation through employee welfare programs by providing incentives. companies can improve employee welfare by adding rest room facilities and places of worship that can create job satisfaction and increase employee productivity.